2015
DOI: 10.2166/aqua.2015.140
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption kinetics and diffusion of Saxitoxins on granular-activated carbon: influence of pore size distribution

Abstract: Saxitoxin (STX) is the most toxic non-protein substance known. STX-producing cyanobacteria have been identified in most continents and are being detected more widely because of global warming, threatening human drinking water supplies worldwide. Removal of these components can be accomplished by adsorption on granular-activated carbon (GAC) but little is yet known about the kinetics of the process. This research investigated adsorption kinetics and diffusion behaviour of a decarbomoyl saxitoxin (dc-STX) and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
0
12
0
1
Order By: Relevance
“…Like PAC, the performance of GAC in the treatment of cyanotoxins depends on the GAC properties which facilitate the electrostatic attraction. The application of GAC in the removal of decarbamoylsaxitoxin (dc-STX) exhibited a repulsive force between positively charged GAC and cationic saxitoxins [50]. Silva Buarque et al [50] further studied the effect of pore size on the adsorption of saxitoxin, and it was found that mesopores played an essential role in promoting adsorption capacity and adsorption kinetics of coconut GAC.…”
Section: Non-agricultural Based Activated Carbonmentioning
confidence: 99%
“…Like PAC, the performance of GAC in the treatment of cyanotoxins depends on the GAC properties which facilitate the electrostatic attraction. The application of GAC in the removal of decarbamoylsaxitoxin (dc-STX) exhibited a repulsive force between positively charged GAC and cationic saxitoxins [50]. Silva Buarque et al [50] further studied the effect of pore size on the adsorption of saxitoxin, and it was found that mesopores played an essential role in promoting adsorption capacity and adsorption kinetics of coconut GAC.…”
Section: Non-agricultural Based Activated Carbonmentioning
confidence: 99%
“…For example, in a recent study by Silva et al, (2015) [76], in a GAC filter treatment, saxitoxin and decarbomoyl saxitoxin (dc-STX) exhibited cationic nature (between mono-cationic and dicationic) in their molecular structure due to the presence of the amine group at neutral pH, which further helped these molecules to get removed due to the electrostatic repulsion [91]. However, these electrostatic repulsions might vary among different cyanotoxins based on the size and charges.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…For example,Tak et al, (2018) [91] it was found that ozone alone (2 mg/L) degraded 68% of anatoxin while ozone with H 2 O 2 and Fe (II) degraded 100% and 85% respectively[108]. The overall mechanism works in a way that hydrogen peroxide in aqueous solution dissociates into HO 2 -which reacts with the ozone molecule providing a chain of reactions to produce more hydroxyl ions.…”
mentioning
confidence: 99%
“…Methanol and water can also be used as solvent as well as supercritical fluids (Haque et al 2017, Pyo et al 2004. Neurotoxins such as saxitoxins can also be adsorbed on powder activated carbon (Ho et al 2009, Westrick et al 2010, Buarque et al 2015. Nevertheless, the desorption can be difficult without molecule damage.…”
Section: Introductionmentioning
confidence: 99%